2015
DOI: 10.1371/journal.pone.0127479
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-High-Throughput Screening of an In Vitro-Synthesized Horseradish Peroxidase Displayed on Microbeads Using Cell Sorter

Abstract: The C1a isoenzyme of horseradish peroxidase (HRP) is an industrially important heme-containing enzyme that utilizes hydrogen peroxide to oxidize a wide variety of inorganic and organic compounds for practical applications, including synthesis of fine chemicals, medical diagnostics, and bioremediation. To develop a ultra-high-throughput screening system for HRP, we successfully produced active HRP in an Escherichia coli cell-free protein synthesis system, by adding disulfide bond isomerase DsbC and optimizing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 41 publications
(43 reference statements)
1
29
0
Order By: Relevance
“…The conditions for expression of enzymatically active HRP in a cell‐free protein synthesis system have been studied previously . To increase the expression level of soluble HRP protein, the N‐terminus of HRP was fused to ubiquitin and its expression was examined under various conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The conditions for expression of enzymatically active HRP in a cell‐free protein synthesis system have been studied previously . To increase the expression level of soluble HRP protein, the N‐terminus of HRP was fused to ubiquitin and its expression was examined under various conditions.…”
Section: Resultsmentioning
confidence: 99%
“…To express HRP or ubiquitinated HRP (ubi‐HRP), the S12 extract was prepared from the E. coli BL21Star(DE3) strain harboring the pK7‐DsbC plasmid that encodes bacterial disulfide isomerase. In addition, the reaction mixture was also supplemented with 16.7 μ m hemin, 2 m m calcium acetate, 100 μ m oxidized glutathione, and 1 m m reduced glutathione . In the experiment that involves in situ cleavage of ubiquitin from ubi‐HRP fusion protein, a mixture of equal volumes of the DsbC‐enriched S12 extract and ubiquitin carboxyl‐terminal hydrolase 1 (UBP1)‐enriched S12 extract was used to perform the cell‐free protein synthesis reactions.…”
Section: Methodsmentioning
confidence: 99%
“…Target genes can be amplified [33] on the beads and expressed via cell-free protein synthesis. [34] Several techniques exist to afterwards bind the protein to its specific DNA on the magnetic bead to generate a covalent genotype-phenotype linkage. [35] Placing the populated magnetic bead then in a compartment in an w/o or a w/o/w emulsion allows for the use of this technique for enzyme evolution as the reaction product remains in the same compartment as the information on the bead -although also alternative linkage…”
Section: Rna Screeningmentioning
confidence: 99%
“…In addition to the advantages of its speed and multiplexibility, the open nature of cell‐free synthesis enables a mix‐and‐match design of protein synthesis using various biological and non‐biological components. For example, a number of studies demonstrated in vitro linkage of genotype and phenotype on the surface of microbeads through cell‐free expression of bead‐immobilized template DNA . Based on a similar concept, through the use of bi‐functionalized microbeads that can capture both the template DNA and the expressed proteins, we were able to physically co‐localize the genes of C. sinensis and their translation products on microbeads .…”
Section: Introductionmentioning
confidence: 99%
“…For example, a number of studies demonstrated in vitro linkage of genotype and phenotype on the surface of microbeads through cell-free expression of bead-immobilized template DNA. [13][14][15] Based on a similar concept, through the use of bi-functionalized microbeads that can capture both the template DNA and the expressed proteins, we were able to physically co-localize the genes of C. sinensis and their translation products on microbeads. 16 The use of microbead-conjugated DNA enabled facile expression and screening of antigenic proteins.…”
Section: Introductionmentioning
confidence: 99%